Studi Literatur Review: Manajemen Zakat Di Benua Asia - Firawati, Putri Ayu (Faculty of Islamic Economics and Business, Madura Islamic State University, 2024)
Abstract: Zakat is obligatory for Muslims who have fulfilled certain requirements and is a form of worship to Allah. Each Asian country has different zakat management. The aim of this research is to describe zakat management in several countries in continent Asia. The research method uses descriptive qualitative literature study (literature review) with collection techniques obtained from journals, books and other supporting documents. The research results show that zakat management in several Asian countries continent is different, where there are several Asian countries continent that require zakat and do not require zakat for their citizens. Apart from that, there are also Asian countries whose management is managed by the state, managed by the private sector, or managed by the state and the private sector simultaneously. Meanwhile, the zakat collected is distributed to groups entitled to receive zakat, namely eight asnaf with a certain priority scale according to the situation and constitution of each country, with zakat distributed in consumptive and productive forms. Keywords: Zakat, Zakat Management. Abstrak: Zakat hukumnya wajib bagi umat Islam yang sudah memenuhi syarat tertentu dan menjadi bentuk ibadah kepada Allah. Setiap negara Asia, memiliki manajemen zakat yang berbeda. Tujuan penelitian ini yaitu untuk mendeskripsikan terkait manajemen zakat dibeberapa negara benua Asia. Metode penelitian mempergunakan deskriptif kualitatif dengan studi kepustakaan (literatur review) dengan teknik pengumpulan didapatkan dari jurnal, buku serta dokumen pendukung lainnya. Hasil penelitian menunjukkan bahwasanya, manajemen zakat pada beberapa negara dibenua Asia berbeda, dimana terdapat beberapa negara benua Asia yang mewajibkan zakat serta tidak mewajibkan zakat pada warga negaranya. Selain itu, terdapat pula negara Asia yang pengelolaannya dikelola oleh negara, dikelola oleh swasta, ataupun dikelola oleh negara serta swasta secara bersamaan. Sementara zakat yang terkumpul didistribusikan kepada golongan berhak menerima zakat yakni delapan asnaf dengan skala prioritas tertentu sesuai situasi dan konsiti tiap negara dengan zakat didistribusikan berbentuk konsumtif serta produktif. Kata Kunci: Zakat, Manajemen Zakat.